Solvability criteria for cubic equations over Z2 - Saburov, Mansoor; Ahmad , Mohd Ali Khameini (American Institute of Physics, 2014)
Solvability criteria for cubic equations over the p-adic field, where p>3, were studied in previous works. For small primes p=2,3, this problem was open. In this paper, we study this problem in the case p=2. The case p=3 would be studied elsewhere in the future.